Praktik Puasa Sunnah dan Pembentukan Self-Regulation Santri di Pondok Pesantren Darul Ilmi Banjarbaru - Badrus Shalih; Marzuqi Marzuqi; Muhammad Iqbal Dewantara; Sahrahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study was motivated by the limited research on the role of voluntary fasting in developing students’ self-regulation, even though Monday–Thursday fasting and Ayyamul Bidh fasting are common practices in Islamic boarding schools (pesantren). The study employed a qualitative method with a phenomenological approach. Data were collected from November to December 2025 through in-depth interviews with seven students (santri), two supervising teachers (ustadz), and one boarding school administrator, supported by observations and document analysis. Data were analyzed using Moustakas’ phenomenological method. The findings reveal that voluntary fasting is understood by the students as a form of self-discipline (mujahadatun nafs) that helps them control their desires, develop time discipline through sahur (pre-dawn meals), worship, study, and breaking the fast, and strengthen their identity as santri. According to the teachers and administrators, students who regularly practice voluntary fasting tend to be more patient, disciplined, less likely to violate school regulations, and more consistent in Qur’anic memorization and muthala’ah (independent study). These findings indicate that voluntary fasting functions not only as a personal act of worship but also as an effective means of spiritual education in fostering students’ self-regulation through the internalization of tazkiyatun nafs (self-purification) values and self-control.